2017
DOI: 10.4149/bll_2016_129
|View full text |Cite
|
Sign up to set email alerts
|

GSM-like radiofrequency exposure induces apoptosis via caspase-dependent pathway in infant rabbits

Abstract: BACKGROUND: There have been several Radio Frequency (RF) fi eld researches on various populations and groups of different ages in recent years. However, the most important group for research has been declared as the pregnant women and their babies. OBJECTIVE: The aim of the study was to analyse the effect on apoptotic factors of RF fi elds on newborn rabbit liver tissues. MATERIALS AND METHODS: Cytochrome c and AIF (Apoptosis Inducing Factor) levels were measured by western blot and caspase 1, 3 and 9 activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…RF EMF is classifi ed as possibly carcinogenic to humans (Group 2B carcinogens) by International Agency for Research on Cancer (IARC) (3). Many studies revealed adverse effects of RF EMF on the cardiovascular, immune and cerebrospinal systems and production of various enzymes and proteins (4)(5)(6)(7)(8). Mobile phone in a calling mode is placed in a close proximity to a user's head that increases absorption of energy by brain (9).…”
Section: Introductionmentioning
confidence: 99%
“…RF EMF is classifi ed as possibly carcinogenic to humans (Group 2B carcinogens) by International Agency for Research on Cancer (IARC) (3). Many studies revealed adverse effects of RF EMF on the cardiovascular, immune and cerebrospinal systems and production of various enzymes and proteins (4)(5)(6)(7)(8). Mobile phone in a calling mode is placed in a close proximity to a user's head that increases absorption of energy by brain (9).…”
Section: Introductionmentioning
confidence: 99%